Hubungan Konsumsi Kopi Kemasan, Tingkat Konsumsi Gizi, dan Kualitas Tidur dengan Persen Lemak Tubuh Mahasiswa - Putri, Allisa Nadhira Permata Arinda (Universitas Airlangga, 2024)
Background: College students are one of the age groups whose nutritional status is important. The percent body fat in a person can be one of the markers that someone is obese or not. The increase in percent body fat mass in students is influenced by several factors, including excessive daily energy intake with the habit of consuming packaged coffee, and poor sleep quality. Objectives: The purpose of this study was to analyze the relationship between packaged coffee consumption, nutritional consumption level, and sleep quality with percent body fat in undergraduate students of the Airlangga University Nutrition Study Program. Methods: This research is a type of analytic observational research using a case-control research design. The sample size used in the study was 52 undergraduate students of Airlangga University Nutrition Study Program, female with a ratio of 26 people for the case group and 26 people for the control group. The sample was obtained using the simple random sampling method. The data that has been obtained is analyzed using a logistic regression test according to the data obtained. Results: The results of the logistic regression test of the independent variables that have the most influence on the dependent variable are the frequency of drinking coffee, the level of fat consumption, and sleep quality. Each significance value and odd ratio generated was p = 0.006 and 0.53 for the frequency of coffee consumption, p = 0.004 and the resulting odd ratio of 11.093 for the level of fat consumption, and p = 0.006 and the odd ratio of 8.985 for sleep quality. Conclusion: Most respondents in the obese group have a higher habit of consuming ready to drink packaged coffee, have poor sleep quality, and consume enough energy and more fat compared to the non-obese group. Overall, the most influential variables with percent body fat are frequency of coffee drinking, fat consumption level, and sleep quality.